Ancient Greece : from prehistoric to Hellenistic times - Martin, Thomas R., 1947- (Yale University Press, 2013)
Offers a comprehensive history of ancient Greece. This title brings alive Greek civilisation from its Stone Age roots to the fourth century B C E. Focusing on the development of the Greek city state and the society, culture, and architecture of Athens in its Golden Age, it integrates political, military, social, and cultural history.